The World Bank's Prototype Carbon Fund and China - ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2004)
As the first global carbon fund, the World Bank's Prototype Carbon Fund (PCF) aims to catalyze the market for project-based greenhouse gas emission reductions while promoting sustainable development and offering a learning-by-doing opportunity to its stakeholders. Since the inception in 2000, the PCF has engaged in a dialogue with China to get it to sign up as a host country, because the World Bank and other international and bilateral donors expect great potential of the clean development mechanism (CDM) in China and feel the significant need for building CDM capacity in China to enable it to gain more insight into the CDM and increase its capacity to initiate and undertake CDM projects. This paper first discusses why China had hesitated to sign up as a host country of PCF projects until September 2003. Then the paper explains what has led China to endorse the PCF projects. The paper ends with discussions on the implications of the PCF's offering prices for the emerging global carbon market.
Keywords: Q54; Q58; Q52; Q48; 330; Carbon prices; Carbon market; China; Prototype Carbon Fund; The World Bank; Klimaschutz; Luftreinhaltung; Investmentfonds; China; Clean Development Mechanism